(untitled) (American Journal of Islam and Society, 2008)
Understanding Islamic philosophy, an indispensable formative link in the chain of medieval thought, is crucial to grasping the intertwined development of philosophical ideas both within and without the Islamic sphere during the period under discussion. Peter Groff and Oliver Leaman’s text belongs to the discipline of the philosophical and theological analysis of Islam. It is an attempt to shed some light on the essential, mainly Islamic contribution to the philosophical thought of the Middle Ages. This work intends to offer “the vital insights and resources of the Islamic philosophical tradition” (p. xi) as a main influence upon medieval philosophic thought in different religions (Judaism and Christianity) and cultures (India). Furthermore, he rightfully refers to Islamic philosophy as a transmitter of the classical Greek legacy. This concise work contains brief entries (alphabetically ordered), key terms, bold marked cross-references to related terms for easy access, and major figures in the rich heritage of Greek, Jewish, Christian, and Muslim philosophy. Each brief entry is written in a very comprehensible style and covers the main relevant ideas related to the theme being discussed. Since religion has always played a decisive role in the development of Islamic thought and was never separated from the state, it is also present in varying degrees in nearly all of the entries. Consequently, this work provides information on the development of Islamic belief. The bibliographical references for further reading at the end of each entry are very helpful, though mostly laconic. Key concepts or terms are given in a simplifiedArabic transcription that differs from the standard one ...